Transilluminations : Making the Transcendent Transparent - Verrips, Jojada (Material religion, 2020)
Chapter 21 of the Book of Revelations contains a detailed description of the New Jerusalem as a city full of divine light and erected on a foundation of brilliant minerals. In the gothic cathedrals built in the Middle Ages this radiant and transcendent place was often represented in their stained glass windows and so made partly visible by the incoming and always changing light. In this contribution light will be shed on the use of stained glass as a translucent medium to make the transcendent transparent. Next to the imagery of the New Jerusalem, attention will be paid to chandeliers representing this holy city as well as to windows with the sacred heart and the remarkable stained glasswork the Belgian artist Wim Delvoye, by many considered to be blasphemous.